PEMBINGKAIAN PEMBERITAAN RESPON PUAN MAHARANI TERHADAP DEMONSTRASI PADA MEDIA KOMPAS.COM DAN TEMPO.CO PERIODE SEPTEMBER-OKTOBER: PEMBINGKAIAN PEMBERITAAN RESPON PUAN MAHARANI TERHADAP DEMONSTRASI PADA MEDIA KOMPAS.COM DAN TEMPO.CO PERIODE SEPTEMBER-OKTOBER - Gabriel Laurence Risakotta; Bryna Trinita Kumala; Milkyway Cookies (Jurnal Komunikasi Dialogis, 2026)
Abstract - The mass media plays a strategic role in shaping public perceptions of political elites' responses to demonstrations, but representations of female figures like Puan Maharani still face the challenge of gender bias. This study examines the framing of news coverage of Puan Maharani's response to the demonstrations by Kompas.com and Tempo.co during the September–October 2025 period. Using a qualitative descriptive approach and Pan & Kosicki's (1993) framing model, this study analyzed 20 online news articles (10 from each media outlet) collected through documentation, based on syntactic, script, thematic, and rhetorical structures. The results show that Kompas.com framed Puan Maharani as an institutional leader who prioritizes stability and dialogue, while Tempo.co presented her as a critical figure who emphasized empathy for the people's aspirations and democratic accountability. These differences in framing reflect the editorial orientations of each media outlet. This research contributes to the study of political communication by explaining the role of framing in shaping public perceptions of the responses of female political elites in the context of social conflict.